"k^2-2k+1=0\\text{ --- auxiliary equation}.\\\\\nk_{1,2}=1\\\\\n\\text{The complementary function:}\\\\\nu=\\phi_1(y+1,x)+x\\phi_2(y+1,x)=\\phi_1(y+x)+x\\phi_2(y+x)\\\\\nf(x,y)=V\\\\\nV\\text{ is a function of x and y}.\\\\\n\\text{Partial integral:}\\\\\np=\\frac{1}{F(D,D\\prime)}V\\\\\np=\\frac{1}{D^2-2DD\\prime+D\\prime^2}(12xy)=\\frac{1}{(D-D\\prime)^2}(12xy)=\\\\\n=\\frac{1}{D^2(1-\\frac{D\\prime}{D})^2}(12xy)=\\frac{12}{D^2}(1-\\frac{D\\prime}{D})^{-2}(xy)=\\\\=\\frac{12}{D^2}(1+\\frac{2D\\prime}{D}+\\frac{3D\\prime}{D^2}+\\ldots)(xy)=\\\\=\\frac{12}{D^2}(xy+\\frac{2}{D}(x)+0\\ldots)=\\\\=\\frac{12}{D^2}(xy)+\\frac{24}{D^3}(x)=12y(\\frac{x^3}{6})+24(\\frac{x^4}{24})=x^4+2x^3y.\\\\\nz=u+p=\\phi_1(y+x)+x\\phi_2(y+x)+x^4+2x^3y."
Comments
Leave a comment